Effects of plant protease inhibitors (Pep-3-EcTI, Pep-BbKI, and Pep-BrTI) versus corticosteroids on inflammation, remodeling, and oxidative stress in an asthma–COPD (ACO) model - João, Juliana Morelli Lopes Gonçalves; Silva Barbosa, Jéssica Anastácia; Sales da Silva, Luana Laura; Fukuzaki, Silvia; de Campos, Elaine Cristina; Camargo, Leandro do Nascimento; Santos, Tabata Maruyama dos; Moreira Bezerra, Suellen Karoline; de Almeida, Francine Maria; Saraiva-Romanholo, Beatriz Mangueira; Lopes, Fernanda Degobbi Tenorio Quirino dos Santos; Bonturi, Camila Ramalho; et al. (Frontiers in Pharmacology, 2024)
The peptides Pep-3-EcTI, Pep-BbKI, and Pep-BrTI exhibit anti-inflammatory and antioxidant activities, suggesting their potential for treating asthma-chronic obstructive pulmonary disease COPD overlap (ACO). We compared the effects of these peptides with dexamethasone (DX) treatment in an ACO model. In this study, 11 groups of male BALB/c mice were pre-treated under different conditions, including sensitization with intraperitoneal injection and inhalation of ovalbumin (OVA), intratracheal instillation of porcine pancreatic elastase (ELA), sensitization with intraperitoneal injection, and various combinations of treatments with peptides (Pep-3-EcTI, Pep-BbKI, Pep-BrTI), DX, and non-treated controls (SAL-saline). Respiratory system resistance, airway resistance, lung tissue resistance, exhaled nitric oxide, linear mean intercept, immune cell counts in the bronchoalveolar lavage fluid, cytokine expression, extracellular matrix remodeling, and oxidative stress in the airways and alveolar septa were evaluated on day 28. Results showed increased respiratory parameters, inflammatory markers, and tissue remodeling in the ACO group compared to controls.Treatment with the peptides or DX attenuated or reversed these responses, with the peptides showing effectiveness in controlling hyperresponsiveness, inflammation, remodeling, and oxidative stress markers.These peptides demonstrated an efficacy comparable to that of corticosteroids in the ACO model. However, this study highlights the need for further research to assess their safety, mechanisms of action, and potential translation to clinical studies before considering these peptides for human use.